Examining the link between weight suppression and non-suicidal self-injurious behaviors. (August 2018) - Keel, Pamela K.; Jean Forney, K.; Buchman-Schmitt, Jennifer M.; Kennedy, Grace A.; Joiner, Thomas E.
Abstract: Background: Given the negative consequences of excess weight, a large portion of the US population is seeking to obtain and maintain weight loss. Weight Suppression (WS) represents the difference between previous highest adult weight and current weight and may have negative psychological consequences. The current study examined the link between WS and lifetime non-suicidal self-injurious (NSSI) behavior and explored indirect effects in this link using survey data in two large samples. Methods: Sample 1 included 1011 college students (67% female, mean age = 19 years); Sample 2 included 2461 participants from an epidemiological study (68% female, mean age = 34 years). Models of direct and indirect effects were tested in MPlus using bootstrapping. Results: As hypothesized, greater WS was associated with increased likelihood of lifetime NSSI in both samples (OR = 1.05 and 1.02). In both samples, significant indirect effects of drive for thinness (Total R 2  = 0.06 and 0.09) and depressive symptoms (Total R 2  = 0.13 and 0.29) accounted for this association. Alternative models in which the indirect effect of WS was tested in associations between drive for thinness or depressive symptoms and NSSI were not supported. Conclusion: Results suggest that the link between WS and lifetime NSSI may be accounted for by eating or mood-related pathology. Future research should test whether addressing associated eating and mood problems would eliminate the link between WS and NSSI as a means for reducing suicide risk. Highlights: Weight suppression was associated with nonsuicidal self-injurious behavior in two samples. Drive for thinness and depression statistically account for this link in both samples. Future work should address eating and mood problems in those attempting to maintain weight loss.